Analysis of The Effect Of Empowerment From A Human Resource Management Perspective On Employee Performance In The South Sibolga District Government - Fauziah Nur Simamora; Yazmal Farhat Pulungan; Parhan Al Parisi; Muhammadfitree Deeyoh (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2026)
Employee empowerment has long been recognized as a pivotal mechanism through which organizations can unlock the full potential of their workforce and, consequently, drive superior organizational outcomes. Within the context of public sector organizations, where bureaucratic structures often constrain individual initiative, the question of how empowerment shapes employee performance takes on added significance. This study was designed to empirically examine the extent to which human resource empowerment influences the performance of civil servants employed at the South Sibolga District Government Office. A descriptive correlational research design was adopted, and data were gathered from 52 civil servants selected through probability sampling from a total population of 109 staff members. The primary data collection instruments comprised structured questionnaires validated through rigorous validity and reliability testing. Pearson product-moment correlation analysis, coefficient of determination, simple linear regression, and t-test were applied to analyze the data using SPSS version 21. The results demonstrate a strong positive relationship between empowerment and employee performance, yielding a correlation coefficient of r = 0.765. The coefficient of determination revealed that empowerment accounted for 58.6% of the variance in employee performance (R² = 0.586). The regression equation Y = 17.592 + 0.668X confirms that each incremental improvement in empowerment is associated with a corresponding increase in performance. Furthermore, the t-test result (t = 8.412 > t-table = 2.008) confirmed statistical significance at the 5% level, leading to rejection of the null hypothesis. These findings suggest that empowering employees through delegated authority, trust-building, access to information, and organizational support represents a strategically important approach to improving civil servant performance. Practical recommendations include institutionalizing empowerment practices within government HR policies and investing in capacity-building programs aligned with civil service competency standards.